Efficacy of Albendazole-Pyrantel Pamoate Compared to Albendazole Alone for Trichuris trichiura Infection in Children: A Double Blind Randomised Controlled Trial - Sapulete, Eva Jacomina Jemima; Dwi Lingga Utama, I Made Gde; Sanjaya Putra, I Gusti Ngurah; Kanya Wati, Dyah; Arimbawa, I Made; Gustawan, I Wayan (The Malaysian journal of medical sciences, 2020)
Soil transmitted helminths (STH) are intestinal nematodes and constitute one of the most neglected tropical diseases to exist. : This study determined the efficacy of albendazole-pyrantel pamoate compared to albendazole in 8-12 years old children with infection. A randomised controlled trial was conducted between October 2017 and February 2018 on participants whose stool examinations confirmed the presence of infection. The subjects were randomised into two groups. The statistical analysis used Chi-square test. There were 392 of 600 children at five public elementary schools in Bangli and Bali and were infected with . The cure rate of infection seven days following treatment was lower with the combination of albendazole and pyrantel pamoate compared to that of albendazole. The egg reduction rate of infection was lower with the combination of albendazole and pyrantel pamoate compared to albendazole. The study indicated that a combination of albendazole and pyrantel pamoate does not improve cure rate or egg reduction rate in 8-12 years old children with infection.